1995
DOI: 10.1148/radiology.194.2.7824737
|View full text |Cite
|
Sign up to set email alerts
|

Female pelvic bone marrow: serial MR imaging before, during, and after radiation therapy.

Abstract: T1-weighted and STIR images obtained during and soon after radiation therapy complement each other in showing changes in bone marrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 0 publications
0
59
0
3
Order By: Relevance
“…In the acute phase, cellular depletion, marrow edema, vascular congestion, and hemorrhage ensue during the first hours and days. Within 1-2 weeks, the observed increase in MR signal intensity in T2-weighted and STIR images is thought to represent a reduction in cellularity and an increase in fat and marrow edema [22,24]. An increase in MR signal on STIR images can be observed as early as 8 days after initiation of RT [22].…”
Section: Post-treatment Changesmentioning
confidence: 99%
See 3 more Smart Citations
“…In the acute phase, cellular depletion, marrow edema, vascular congestion, and hemorrhage ensue during the first hours and days. Within 1-2 weeks, the observed increase in MR signal intensity in T2-weighted and STIR images is thought to represent a reduction in cellularity and an increase in fat and marrow edema [22,24]. An increase in MR signal on STIR images can be observed as early as 8 days after initiation of RT [22].…”
Section: Post-treatment Changesmentioning
confidence: 99%
“…7) [22]. In the spine, a band pattern of peripheral, intermediate T1 signal intensity has also been noted, and is thought to represent red marrow surrounding a central fatty deposit [24].…”
Section: Post-treatment Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies (Romanos et al 2013 ;Blomlie et al 1995 ) have reported that radiation-induced changes with small but measurable fatty conversion may occur outside the irradiation fi eld but the etiology and signifi cance of such changes remain unclear. The bone marrow outside the irradiation fi eld may show similar MRI signal changes compared to bone marrow within the irradiation fi eld but to a much lower degree.…”
Section: Radiation-induced Changes On Normal Bone Marrowmentioning
confidence: 99%